Entomobalia new genus, the first member of Nycteliini (Coleoptera: Tenebrionidae) from Brazil - Flores, Gustavo Ernesto (2002)
Entomobalia, new genus (Pimeliinae: Nycteliini) is described from northeastern Brazil and is the first genus of the tribe Nycteliini recorded for that country. This new genus is created on the basis of two previously described species: Asida platynotos Perty and Asida picta Perty (new combinations in Entomobalia), formerly placed in the genus Scotinus Kirby (Pimeliinae: Asidini). Sixteen different character states among the species of Scotinus and the two species assigned to Entomobalia are discussed, 11 of which are shared by Entomobalia with all or some genera of Nycteliini and not with the remaining species of Scotinus. A description for the genus and redescriptions of the two species are provided. Main diagnostic characters for Entomobalia are in sexual dimorphism and male and female genitalia. Habitus photographs, illustrations of external morphology, internal skeletal anatomy, genitalic features, and a distribution map are included.